Firmes nos propósitos : etnografia da internação de usuários de drogas em comunidades terapêuticas - Nunes, Matheus Caracho (2016)
Currently, therapeutic communities (TCs), play a key role in crack users management and other drugs under the current public policies. Against this background, this research focuses three therapeutic communities of diferent regions in Brazil. Two located in medium-sized cities in the interior of the state of São Paulo and another in a medium-sized city in the interior of the state of Pernambuco. This dissertation presents the descriptive objective of demonstrating the internal dynamics of these therapeutic communities. Unfolds this two objectives: i) know the practices and results of the therapies used; ii) know the profile of inmates, employees and operators, above all, to know the daily life inside them. As a result, the therapeutic communities researched intend to create conditions for the change of subjects that are considered as addicts, proposing (re) creating the conditions of social interaction of subjects through activities centered on the axes of spirituality, work and discipline. They contribute, therefore, to the perpetuation of an individual and guilty perspective of the drug question. The text is supported by ethnographic work that includes: i) interspersed visits made since 2012; ii) immersion in the field performing three periods of fifteen days one in each institution.